Efek Tryadic Communication Pura Samuantiga Dalam Pemujaan Tri Murti Di Bali - I Wayan Wirta; Sintyananda Gayatri (Jayapangus Press, 2022)
There has been a conflict of understanding among Hindu religious groups, as a result of not adapting to the local cultural environment that has been considered well established. So as a consequence, there is a gap/conflict of understanding that has an impact on miscommunication. The concerns of various parties, especially among traditional Hindu figures as the